Portable solar photovoltaic systems for post-disaster emergency power supply: a comprehensive review - Sutikno, Tole; Aji, Wahyu Sapto; Facta, Mochammad; Purnama, Hendril Satrian; Wahono, Tri (Institute of Advanced Engineering and Science, 2025)
Natural disasters frequently disrupt electrical infrastructure, creating critical challenges for emergency response, healthcare delivery, and community recovery. Portable solar photovoltaic (PV) systems have emerged as a sustainable and rapidly deployable solution for off‑grid energy provision in disaster‑affected regions. This review provides a comprehensive synthesis of portable PV technologies for post‑disaster applications, encompassing system architectures, component selection, deployment configurations, and operational performance. Particular emphasis is placed on DC‑first designs, modular scalability, energy storage integration, and IoT‑enabled monitoring, which collectively enhance efficiency, reliability, and usability under harsh environmental conditions. The analysis highlights persistent challenges related to energy efficiency, storage resilience, system standardization, and user accessibility, while underscoring the importance of integration into broader emergency energy ecosystems. Research gaps are identified in areas such as efficiency optimization, human‑centered design, and scalability, providing guidance for the development of next‑generation portable PV systems. By consolidating technical and operational insights, this review establishes a foundation for advancing portable PV systems as robust emergency energy solutions, bridging the gap between immediate relief and long‑term resilience in disaster‑prone regions.